Risk factors assessment in non-insulin-dependent diabetes mellitus women: a cross sectional study from Telangana - Shruti, P.; Joshi, K. P.; Takalkar, Anant A. (International Journal Of Community Medicine And Public Health, 2019)
Background: The prevalence of women with type-2 diabetes mellitus in Karnataka is 22.04%. Many people are diagnosed type-2 diabetes in their teens or early 20s. And with advancing age, the risk of getting type-2 diabetes goes up too, especially if you don’t change any of the diabetes risk factors like your weight and physical activity level. Women who get type-2 diabetes are at greater risk than men of cardiovascular disease and blindness. The objective of the study was to study the risk profile amongst diabetic females. Methods: The hospital-based descriptive observational study was carried out in 75 non-insulin-dependent diabetes mellitus (NIDDM) women at Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar from June 2010 to December 2010. Detailed history and anthropometric assessment was done and data analysed with SPSS software. Results: Majority of the diabetic women were from 40-50 years age group i.e. 33 (44%). Mean age was seen as 52±12.4 years. 57 women having sedentary lifestyle (76%). Mean BMI was found to be 24.58±5.27 kg/m2. Waist circumference was 83.42±9.35 cm. Hip circumference was 95.05±9.1 cm and waist/hip ratio was 0.877±0.041. Conclusions: Increasing age, sedentary lifestyle, obesity especially central and obstetric events were found to be important risk factors in our study.